2019
DOI: 10.1186/s13054-019-2706-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between hydroxocobalamin administration and acute kidney injury after smoke inhalation: a multicenter retrospective study

Abstract: BackgroundThe use of hydroxocobalamin has long been advocated for treating suspected cyanide poisoning after smoke inhalation. Intravenous hydroxocobalamin has however been shown to cause oxalate nephropathy in a single-center study. The impact of hydroxocobalamin on the risk of acute kidney injury (AKI) and survival after smoke inhalation in a multicenter setting remains unexplored.MethodsWe conducted a multicenter retrospective study in 21 intensive care units (ICUs) in France. We included patients admitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 18 publications
(20 reference statements)
1
12
0
Order By: Relevance
“…Although generally regarded safe, widespread use of hydroxocobalamin as a first-line agent for cyanide poisoning has been questioned by some. 1 A multicenter retrospective study from France found that hydroxocobalamin use in patients with smoke inhalation did not confer a survival advantage and was associated with increased risk of severe AKI and renal replacement therapy. 1 The etiology of AKI in these patients was unclear because renal biopsies were not performed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although generally regarded safe, widespread use of hydroxocobalamin as a first-line agent for cyanide poisoning has been questioned by some. 1 A multicenter retrospective study from France found that hydroxocobalamin use in patients with smoke inhalation did not confer a survival advantage and was associated with increased risk of severe AKI and renal replacement therapy. 1 The etiology of AKI in these patients was unclear because renal biopsies were not performed.…”
Section: Discussionmentioning
confidence: 99%
“… 1 A multicenter retrospective study from France found that hydroxocobalamin use in patients with smoke inhalation did not confer a survival advantage and was associated with increased risk of severe AKI and renal replacement therapy. 1 The etiology of AKI in these patients was unclear because renal biopsies were not performed. In another study, hydroxocobalamin administration was associated with a significant risk of AKI and elevated urine oxalate levels in critically ill patients with burns, 2 of whom had oxalate nephropathy on renal biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients were categorized into the AKI group (KDIGO stage 3) if they received continuous renal replacement therapy (CRRT) within the first 7 days after ICU admission. Severe AKI was defined as KDIGO stage 2 or higher, otherwise it was defined as mild AKI ( 22 , 23 ). Secondary outcomes included the ICU and hospital mortality, which were defined as the occurrence of death during the ICU and hospital stay, respectively.…”
Section: Methodsmentioning
confidence: 99%